Jesus and the empire of God: royal language and imperial ideology in the Gospel of Mark - Froelich, Margaret (Library of New Testament studies, 2022)
"Margaret Froelich argues that the Gospel of Mark portrays the Kingdom of God as a conquering empire and Jesus as its victorious general and client king"--